Genetic and Targeted eQTL Mapping Reveals Strong Candidate Genes Modulating the Stress Response During Chicken Domestication. Issue 2 (1st February 2017) - Fallahsharoudi, Amir; de Kock, Neil; Johnsson, Martin; Bektic, Lejla; Ubhayasekera, S J Kumari A; Bergquist, Jonas; Wright, Dominic; Jensen, Per
Abstract: The stress response has been largely modified in all domesticated animals, offering a strong tool for genetic mapping. In chickens, ancestral Red Junglefowl react stronger both in terms of physiology and behavior to a brief restraint stress than domesticated White Leghorn, demonstrating modified functions of the hypothalamic–pituitary–adrenal (HPA) axis. We mapped quantitative trait loci (QTL) underlying variations in stress-induced hormone levels using 232 birds from the 12th generation of an advanced intercross between White Leghorn and Red Junglefowl, genotyped for 739 genetic markers. Plasma levels of corticosterone, dehydroepiandrosterone (DHEA), and pregnenolone (PREG) were measured using LC-MS/MS in all genotyped birds. Transcription levels of the candidate genes were measured in the adrenal glands or hypothalamus of 88 out of the 232 birds used for hormone assessment. Genes were targeted for expression analysis when they were located in a hormone QTL region and were differentially expressed in the pure breed birds. One genome-wide significant QTL on chromosome 5 and two suggestive QTL together explained 20% of the variance in corticosterone response. Two significant QTL for aldosterone on chromosome 2 and 5 (explaining 19% of the variance), and one QTL for DHEA on chromosome 4 (explaining 5% of the variance), were detected. Orthologous DNA regions to the significant corticosterone QTL have been previously associated with the physiological stress response in other species but, to our knowledge, the underlying gene(s) have not been identified. SERPINA10 had an expression QTL (eQTL) colocalized with the corticosterone QTL on chromosome 5 and PDE1C had an eQTL colocalized with the aldosterone QTL on chromosome 2. Furthermore, in both cases, the expression levels of the genes were correlated with the plasma levels of the hormones. Hence, both these genes are strong putative candidates for the domestication-induced modifications of the stress response in chickens. Improved understanding of the genes associated with HPA-axis reactivity can provide insights into the pathways and mechanisms causing stress-related pathologies.